Farmer's Perception on Agrotourism Development of Kemuninglor Village - Muksin Muksin; M Farhan; NBE Sulistyono; FR Diayana (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Rembangan is an agrotourism location that is visited by many tourists. Rembangan is part of Kemuning Lor Village, Arjasa Subdistrict managed by the Jember regional government. Rembangan agrotourism focuses on people's farming in low-temperature areas, livestock and cow's milk producers. The increasing exploration of agriculture and other people's businesses, will have an impact on the sustainability of Rembangan as agrotourism. Agrotourism sourced from the exploration and empowerment of resources and local communities will tend to exist and be sustainable to make agrotourism in Kemuning Village as a tourist icon needs to be done agrotourism development there. Therefore, it is necessary to do devotion to find out how the perception of farmers and the level of participation of farmers if agrotourism development is carried out there. The Population is all farmers in Kemuning Lor Village. The determination of the sample was done using a sampling cluster of 50 farmers of Kemuning Lor village. The methods of activities are literature studies, location observation, unstructured interviews, training, and the creation of learning and socialization instruments. The results of the civil services activities show that the perception of farmers is positive in the development of agrotourism. Has a positive influence on the level of participation of farmers in the development of agrotourism in Kemuning Lor Village. The community is willing and committed to assistance and monitoring and evaluation in the development of agrotourism together with the entire agrotourism circle community. The development of agrotourism must be in collaborated among stakeholders as one of the sources of income.